Establishing a skills laboratory in a Brazilian University Hospital: introducing clinical simulation for pediatric emergencies - Belluomini, Fernando; de Melo Alexandre Fraga, Andrea; Marson, Fernando Augusto Lima; Mello, Lucas Silva; Costa, Patrícia Teixeira; Colbachini, Paulo Cesar Massucatto; Bicudo, Angélica Maria (Frontiers in Medicine, 2025)
BackgroundThe history of Emergency Pediatrics at the University of Campinas (Unicamp of the Portuguese Universidade de Campinas) began in 1986, with the creation of the Discipline of Emergency Pediatrics in the Department of Pediatrics. This development was driven by the growing need for specialization in childcare, given the physiological differences and the specific attention required in emergencies. In the 1980s, the Pediatric Advanced Life Support (PALS) program played a crucial role in improving pediatric emergency care. Training in the area was formally regulated in 2016, after a period of interruption in the 2000s.MethodsThis informative article was designed with the objective of underscoring the importance of establishing a skills laboratory within a university hospital center. To achieve this, we reviewed institutional records, the history of residency programs, and national and international initiatives that supported the inclusion of simulation in medical education. Special attention was given to the evolution of medical simulation, its integration into the Unicamp curriculum, and its application in pediatric emergency training.ResultsUnicamp pioneered the creating of a residency program in Pediatric Emergency, consolidating its training with internships in Intensive Care Units and Anesthesiology. Since 1986, the Pediatric Emergency Room has been coordinated by institutional professionals and was strengthened with the start of the residency program in 1991. Training expanded with the creation of an outpatient clinic for graduates, and in 2018, 24 professionals were awarded the title of Pediatric Emergency Physician, three of them from Unicamp. Currently, 12 graduates are working in different regions of Brazil. Regarding simulation, Brazil began using this educational technique in the 1990s, initially in nursing courses. Following the World Health Organization’s recognition in 2009 of its importance in controlled training environments, and subsequent initiatives by the Ministry of Health and the Pan American Health Organization in 2014, medical simulation was progressively incorporated into Brazilian medical schools. At Unicamp, the implementation began in 2007 with the construction of the Center for Realistic Simulation, inaugurated in 2009. Since then, medical students and pediatric residents have participated in high-fidelity simulation sessions, strengthening both technical and non-technical skills such as communication and teamwork.ConclusionThe experience of Unicamp demonstrates that the establishment of a skills laboratory within a university hospital contributes significantly to the advancement of medical education, the consolidation of pediatric emergency residency training, and the improvement of healthcare delivery. Medical simulation, fully integrated into the curriculum, has proven to be an essential tool not only for developing clinical competencies but also for fostering professional collaboration, thereby strengthening the overall quality of pediatric emergency care.